Genetic diversity determined by agronomic traits and SSR markers in two South American orange‐fleshed sweetpotato breeding populations with potential for population hybrid breeding - Diaz, F.; Eyzaguirre, R.; David, M.; Sevillano, R.B.; Low, Jan W.; Grüneberg, W.J. (Wiley, 2022)
Orange-fleshed sweetpotato (OFSP) breeding populations have gained importance for food security and health reasons. This study's main objectives were to determine genetic diversity in parental material of two OFSP populations (PJ and PZ) relative to mega-clones (MCs) using agronomic traits and simple sequence repeat (SSR) markers and to determine whether PJ and PZ are mutually heterotic by developing a PJ × PZ hybrid population (H0). Field trials were performed with clones for PJ (N = 49), PZ (N = 31), MC (N = 21), and H0 (N = 6898) in Peru. Traits recorded were storage root yield (RYTHA), number of commercial roots per plant, foliage yield, biomass, harvest index, and dry matter (RDM), β-carotene (RBC), protein, starch, sucrose, iron, zinc, and calcium content of storage roots. Sixty-six pairs of SSR primers were used to determine molecular diversity. Statistics used were linear mixed models, principal component analysis, and standard procedures for molecular data. New genetic variation was found in PJ and PZ (e.g. RDM ≥ 29% with RBC ≥ 25 mg 100g−1 dwb). For most traits, genetic variance in PJ and PZ was as large as in MC. The SSR marker data clearly separated PJ and PZ into two gene-pools, together covering nearly the entire MC molecular diversity. Average RYTHA in H0 was high (40.7 t ha−1) with average heterosis increment of 21.8% and range −30.6% to 139.4%. The PJ and PZ lend themselves to study of the efficiency of reciprocal recurrent selection in sweetpotato population hybrid breeding.